Perception and acceptability towards HPV vaccination among mothers of adolescent girls employed in health care sector-a cross sectional study - Shipra Saini; Ritu Nagar; Mithilesh Kumar; Himanshu Shekhar; Pooja Goyal (Clinical Epidemiology and Global Health)
Background: Raising awareness among parents of adolescent girls and addressing misconceptions is crucial to overcoming HPV vaccine hesitancy and ensuring the success of vaccination programs, ultimately reducing the burden of cervical cancer. Objective: To assess perceptions of HPV infection and identify factors influencing the acceptability of the HPV vaccine among female healthcare staff with at least one adolescent daughter. Methods: Female healthcare staff with at least one unmarried adolescent daughter were interviewed using a pre-tested semi-structured questionnaire after obtaining written informed consent. Participants without prior knowledge were provided information before questions on vaccine willingness were asked. Data analysis was conducted using SPSS, with categorical variables presented as proportions and Chi-square tests applied at a 5 % significance level. Results: A total of 102 female staff members were interviewed. While 76 % had heard of cervical cancer, only 32.4 % were aware of HPV infection, and 14.7 % knew about its transmission. Awareness of HPV vaccination was primarily through healthcare providers, with only 36.2 % knowing of its availability. Factors such as age, education, occupation, and socioeconomic status significantly influenced perceptions of HPV infection and awareness of cervical cancer. Willingness for vaccination was strongly associated with occupation and socioeconomic status. Conclusion: Despite gaps in understanding HPV and its connection to cervical cancer, there is high willingness to accept the vaccine. Enhancing mass awareness, especially among parents of adolescents through media and healthcare providers, is vital. Efforts should focus on integrating the HPV vaccine into Universal Immunization Programs, particularly within school health services.